Unusual cause of ear wax - Malhotra, Sonali (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Sir, We were provoked to write this short piece after we encountered around 50 cases presenting to us in Otorhinolaryngology OPD (from August 2020 till May 2021) at our institution with an atypical cause of ear wax. The current COVID-19 pandemic has imposed the worldwide use of masks in addition to social distancing. With this background, we present an interesting cause of ear wax. We had 186 patients coming to the OPD with ear wax out of which only 50 adult patients never had accumulation of wax before. Patients using ear buds on regular basis, using earphones/ headphones for prolonged durations i.e., more than one hour/day, history of ear discharge or any otological surgeries in the past, using masks with strings were excluded from the study.